2020
DOI: 10.3847/1538-4357/ab6dcf
|View full text |Cite
|
Sign up to set email alerts
|

Is the High-Resolution Coronal Imager Resolving Coronal Strands? Results from AR 12712

Abstract: Following the success of the first mission, the High-Resolution Coronal Imager (Hi-C) was launched for a third time (Hi-C 2.1) on 29 th May 2018 from the White Sands Missile Range, NM, USA. On this occasion, 329 seconds of 17.2 nm data of target active region AR 12712 was captured with a cadence of ≈ 4 s, and a plate scale of 0.129 pixel. Using data captured by Hi-C 2.1 and co-aligned observations from SDO/AIA 17.1 nm we investigate the widths of 49 coronal strands. We search for evidence of substructure withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 52 publications
13
69
1
Order By: Relevance
“…White arrows indicate the fingers in each panel. The widths of each finger in the Si iv 1394 Å channel was less than 1 (similar to the inferred widths of coronal loops in the highest resolution coronal imaging currently available; Williams et al 2020) and the lengths were between 3-5 . The lifetimes of these fingers ranged from a few minutes to more than half an hour.…”
Section: Potential Links To Coronal Loopssupporting
confidence: 54%
“…White arrows indicate the fingers in each panel. The widths of each finger in the Si iv 1394 Å channel was less than 1 (similar to the inferred widths of coronal loops in the highest resolution coronal imaging currently available; Williams et al 2020) and the lengths were between 3-5 . The lifetimes of these fingers ranged from a few minutes to more than half an hour.…”
Section: Potential Links To Coronal Loopssupporting
confidence: 54%
“…Due to LOS integration of optically thin EUV emission it is difficult to interpret fine structure in transverse intensity profiles, particularly when using a single channel as may be the case for coronal loops which are often identifiable only in the 171 Å channel of SDO/AIA. Observations using higher resolution instruments such as CRisp Imaging Spectro-Polarimeter (CRISP; Antolin et al, 2012;Scullion et al, 2014) and the High-Resolution Coronal Imager (Hi-C; Aschwanden and Peter, 2017;Williams et al, 2020) reveal that loop structuring indeed exists below the resolution of SDO/AIA. Our results demonstrate that the non-linear evolution of the loop profile by KHI produces a time-dependent (increasing) damping rate for kink oscillations that would not be expected for structuring due to loops being multi-stranded.…”
Section: Discussionmentioning
confidence: 99%
“…2 Philishvili et al: Flow patterns However, the observations of smaller scale flows are rather puzzling as most of these flows are of the order of a few times the spatial resolution limit, provided by the instruments on the abovementioned space missions. Recently, Williams et al (2020) reported the discovery of a large population of so-called coronal strands in active regions made with the High-Resolution Coronal Imager (Hi-C 2.1, with 0 .129 pixel −1 resolution, see Rachmeler et al (2019)), which is the advanced version of the original Hi-C NASA sounding rocket experiment performed in 2012 (Kobayashi et al 2014). The existence of these strands reveals that large-scale magnetic objects like active regions have fine small-scale structures.…”
Section: Introductionmentioning
confidence: 99%
“…As to the aperiodic motions of the observed intensity blobs in the same active region (AR11429), these are the main objective of the present study. In particular, we aim to formulate a mathematically rigorous identification and statistical classification method using SDO/AIA 171Å for flows in the small-scale strands of similar spatial scales as those observed with the higher resolution instruments (Williams et al 2020). Our proposed method provides a set of identified aperiodic flow trajectories together with their estimated velocity bounds (taking into account corrections in pixel distances due to the projection deformation of the solar spherical surface in flat CCD images) and classification as either subsonic, sonic, or supersonic.…”
Section: Introductionmentioning
confidence: 99%